Consumers' knowledge and readiness to accept the implementation of mandatory Malaysia halal certification scheme (MHCS) - Abu Bakar, Ibrahim; Man, Sa'adan (IIUM Press, International Islamic University Malaysia, 2023)
Abstract: Food Industries in Malaysia have implemented the Malaysian Halal Certification Scheme (MHCS) on voluntary basis for more than 49 years. This long experience should be exploited to boost the implementation of mandatory MHCS involving all categories of food premises. Aim: This study aimed to analyze the level of knowledge and readiness of consumers in Malaysia to accept the implementation of mandatory MHCS by food industries. Methods: The study was quantitatively conducted involving consumers who were structured and randomly selected from five different zones in Malaysia. All the study data were collected using a specific pre-tested questionnaire and analyzed using the statistical computer program SPSS 25.0 (Windows). Results: The results of the study show that the level of knowledge and readiness of consumers in Malaysia toward the implementation of mandatory MHCS is at a satisfactory level or at a medium-high level. The knowledge and readiness status of Malay Muslim consumers is higher than non-Malay and non-Muslim consumers. Conclusion: The consumers’ knowledge level could be used to indicate country readiness in implementing mandatory MHCS.